2018
DOI: 10.1177/0192623318775023
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of New Urinary Translational Safety Biomarkers of Drug-induced Renal Tubular Injury in Tenofovir-treated Cynomolgus Monkeys and Beagle Dogs

Abstract: Newer urinary protein kidney safety biomarkers can outperform the conventional kidney functional biomarkers blood urea nitrogen (BUN) and serum creatinine (SCr) in rats. However, there is far less experience with the relative performance of these biomarkers in dogs and nonhuman primates. Here, we report urine protein biomarker performance in tenofovir-treated cynomolgus monkeys and beagle dogs. Tenofovir intravenous daily dosing in monkeys for 2 or 4 weeks at 30 mg/kg/day resulted in minimal to moderate tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…As an example, urinary b2-microglobulin has frequently been used for the detection of kidney toxicity induced by both ASOs and other modalities. 32,43,51 As reported in Supplemental Material, in our study, this biomarker increased in a dose-dependent manner after tool ASO administration. Further work is needed to verify if the FDA-qualified kidney biomarker panel should be complemented by additional biomarkers in Figure 6.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As an example, urinary b2-microglobulin has frequently been used for the detection of kidney toxicity induced by both ASOs and other modalities. 32,43,51 As reported in Supplemental Material, in our study, this biomarker increased in a dose-dependent manner after tool ASO administration. Further work is needed to verify if the FDA-qualified kidney biomarker panel should be complemented by additional biomarkers in Figure 6.…”
Section: Discussionsupporting
confidence: 87%
“…The early KIM-1 increases in our study are in line with reports of similar rapid inductions seen in rodents with several nephrotoxins that are also known to target proximal tubules. 8,13,35,43,44 The expression of KIM-1 and NGAL has been shown to increase after kidney injury in proximal tubule epithelial cells, which initiate proliferation and migration to damaged areas, reflecting a regenerative response. [45][46][47] Unexpectedly, treatment with control ASO also induced elevations in several biomarkers, but to a lesser extent than a similar dose of the tool ASO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in animal models have demonstrated that several of these biomarkers outperformed traditional measures of kidney function in detecting the onset and progression of histologicallyconfirmed TDF-associated tubular injury. [59] Future studies exploring this methodology should include comparisons of the long-term renal impact of TDF and TAF to inform risk stratification and judicious allocation of the newer formulation of tenofovir. To distinguish tenofovir toxicity from other etiologies of kidney injury, future studies should also characterize longitudinal biomarker profiles associated with other kidney disease risk factors among HIV-infected persons.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent efforts have demonstrated the added value of novel kidney biomarkers in monitoring kidney injury, relative to the traditional blood biomarkers such as blood urea nitrogen (BUN) and serum creatinine (SCr). [8][9][10][11][12][13][14] Here, we provide a detailed characterization of drug-induced histomorphologic changes in the NHP kidney and conventional clinical chemistry alterations in blood following dosing with nephrotoxic pharmaceuticals and provide further insight to the corresponding performance of 10 urinary biomarkers. The urinary biomarkers selected included albumin, clusterin, cystatin C, KIM-1, livertype fatty acid-binding protein (L-FABP), N-acetyl-b-Dglucosaminidase (NAG), neutrophil gelatinase-associated lipocalin (NGAL), osteopontin (OPN), retinol binding protein 4 (RBP4), and total protein.…”
Section: Introductionmentioning
confidence: 99%